1999
DOI: 10.1038/sj.leu.2401408
|View full text |Cite
|
Sign up to set email alerts
|

The KOR-SA3544 antigen predominantly expressed on the surface of Philadelphia chromosome-positive acute lymphoblastic leukemia cells is nonspecific cross-reacting antigen-50/90 (CD66c) and invariably expressed in cytoplasm of human leukemia cells

Abstract: We previously reported a novel monoclonal antibody KOR-SA3544 which predominantly reacted with a surface antigen (sSA3544) expressed on Philadelphia chromosome (Ph1)-positive acute lymphoblastic leukemia (ALL). In the present study, we demonstrate that the antibody specifically recognized nonspecific cross-reacting antigen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…61,62 An interesting observation in this context is that CEAs have been shown to be aberrantly expressed in ALL, preferentially in Philadelphia (Ph)-positive cases. 63 Furthermore, a monoclonal antibody (KOR-SA3544), later identified as CEACAM6, 64 was shown to react with all 26 investigated Ph-positive ALL cases, but only with a minority of Ph-negative ALL and AML. 65 Needless to say, however, further studies are needed before a firm conclusion can be made on mechanisms behind the observed upregulation of CEACAM1 by BCR/ABL.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 An interesting observation in this context is that CEAs have been shown to be aberrantly expressed in ALL, preferentially in Philadelphia (Ph)-positive cases. 63 Furthermore, a monoclonal antibody (KOR-SA3544), later identified as CEACAM6, 64 was shown to react with all 26 investigated Ph-positive ALL cases, but only with a minority of Ph-negative ALL and AML. 65 Needless to say, however, further studies are needed before a firm conclusion can be made on mechanisms behind the observed upregulation of CEACAM1 by BCR/ABL.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, malignant cells in precursor B-ALL patients can be distinguished from normal early B-lineage cells based on atypical immunological characteristics. This concerns tumour-associated ectopic expression of antigens such as TdT, CD66c or NG2, crosslineage antigen expression, maturational asynchronous antigen expression, antigen overexpression or loss of markers expressed in normal B-cell precursors (Van Dongen et al, 1996;Dworzak et al, 1998b;Ciudad et al, 1999;Sugita et al, 1999). Such characteristics can be detected with currently available four-colour flow cytometry in at least 85% of the cases (Wells et al, 1998;Campana & CoustanSmith, 1999;Lucio et al, 1999;Weir et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This antigen has not yet been studied in the workshops on human leukocyte differentiation antigens (HLDA). However, a study by Sugita et al 116 showed that the KOR-SA3544 mAb reacts with CD66c (synonym, NCA50/90), a member of the carcinoembryonic antigen (CEA) family. CD66c is expressed by normal granulocytes and is constantly lacking in normal lymphocytes.…”
Section: Cea Family Member Correlating With Three Genotypesmentioning
confidence: 99%